Increased Long-Term Mortality among Black CABG Patients Receiving Preoperative Inotropic Agents - Efird, Jimmy T.; Griffin, William F.; Sarpong, Daniel F.; Davies, Stephen W.; Vann, Lulia; Koutlas, Nathaniel T.; Anderson, Ethan; Crane, Patricia B.; Landrine, Hope; Kindell, Linda; Iqbal, Zahra J.; Ferguson, T. Bruce; et al. (My University, 2015)
The aim of this study was to examine racial differences in long-term mortality after coronary artery bypass grafting (CABG), stratified by preoperative use of inotropic agents. Black and white patients who required preoperative inotropic support prior to undergoing CABG procedures between 1992 and 2011 were compared. Mortality probabilities were computed using the Kaplan-Meier product-limit method. Hazard ratios (HR) and 95% confidence intervals (CI) were computed using a Cox regression model. A total of 15,765 patients underwent CABG, of whom 211 received preoperative inotropic agents within 48 hours of surgery. Long-term mortality differed by race (black versus white) among preoperative inotropic category (inotropes: adjusted HR = 1.6, 95% CI = 1.009–2.4; no inotropes: adjusted HR = 1.15, 95% CI = 1.08–1.2; Pinteraction < 0.0001). Our study identified an independent preoperative risk-factor for long-term mortality among blacks receiving CABG. This outcome provides information that may be useful for surgeons, primary care providers, and their patients.
Keywords: inotropes, cardiac surgery, mortality, disparities, heart disease, heart failure